O USO DA CALCULADORA NAS AULAS DE MATEMÁTICA NA 8ª SÉRIE DO ENSINO FUNDAMENTAL - Schiffl, Daniela (2007)
This paper investigates the use of calculators, in Mathematics classes, in the 8th grade of Elementary School, focusing the teaching of Simple and Compound Interest. It is a qualitative exploratory research that looks for the opinion of docents, students and future teachers, from Elementary and High School , about this subject and proposes a methodology, indicating the calculator as an auxiliary tool to solve mathematical calculus. Data were collected from questionnaires applied to docents and future teachers from Elementary and High School, and from the observations made by the students about the used methodology. To develop this paper, we made a brief historic about the use of calculator, and after we discussed favorable and unfavorable aspects of its use. Besides, Mental Calculus was treated as a strategy to be allied to the use of calculator to teach Interest. Because of this, in this paper we present two proposals to use calculators in class: the first one works with Simple and Compound Interest and the second one has introductory activities, linking mental calculus and calculator. Data analysis suggests that the use of calculator is well accepted among students and academics and it is little accepted by docents. It also shows that students have difficulties to solve mathematical problems and, rarely, use mental calculus. This research suggests the use of calculator if it is supported by mental calculus.